PENGARUH MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE TERHADAP MOTIVASI BELAJAR SISWA KELAS V MATA PELAJARAN IPAS SDN 124 MAMPOTU KECAMATAN AMALI KABUPATEN BONE - Rosmalah, Rosmalah; Kadir, Abd; Wahab, Ernina N (MACCA : Science-Edu Journal, 2025)
This quantitative research used a pre-experimental design, specifically the One Group Pretest-Posttest Design, to examine the differences and significant effects of learning motivation before and after implementing the IOC learning model on fifth-grade students of IPAS at SDN 124 Mampotu, Amali District, Bone Regency. The variables in this study were the IOC model (independent variable) and learning motivation (dependent variable). The population of this study consisted of all fifth-grade students at SDN 124 Mampotu, totaling 30 students. The sampling technique used was saturated sampling. The data were collected through questionnaires. The data collection technique used was a test to determine students' learning motivation before and after implementing the IOC learning model. Based on statistical analysis, the pretest average score was 49.00, indicating that students' learning motivation was in the low category, while the posttest average score was 74.90, which fell into the moderate category. The conclusion of this study indicates that there are significant differences and effects on students' learning motivation before and after implementing the IOC learning model on fifth-grade students of IPAS at SDN 124 Mampotu, Amali District, Bone Regency."